EMPOWERING TRANSLATION: PERFORMATIVE MASCULINITY PORTRAYED IN ROBERT BADEN-POWELL’S SCOUTING FOR BOYS - Wibisono Yudhi Kurniawan; Adi Sutrisno (Program Studi Pendidikan Bahasa Indonesia, Institut Pendidikan Nusantara Global, 2024)
Given the disempowered status of translation as is shown in the fact that it is typically regarded or treated as secondary, derivative, and thus inferior, the necessity to further explore ways to empower translation needs to be recognized and reaffirmed. This study aimed at investigating the untranslatability of masculinity, transcultural practice of cultural word-loaded translation, and performative masculinity found in Robert Baden Powell’s Scouting for Boys from English into Indonesian since not all cultural terms in Source Text can be fully transferred into Target Text as well as the translator’s decision to overcome the problem of untranslatability since English and Indonesian have very different cultural concepts. In this qualitative descriptive study, the data in the forms of words, phrases, or sentences denoting performative masculinity have been taken from the book of Robert Baden Powell’s Scouting for Boys. The results show that when the aforementioned study found that the loan word or loan word plus explanation strategy can be used to deal with the problem of untranslatability. Every strategy, procedure, and method offer a solution to translation difficulties, one of which is retaining words from the source text into the target text via transference, naturalization, and notes to untranslatability of masculinity, transcultural practice in cultural word-loaded translation, and performative masculinity. Translation must and can be empowered, and to avoid weak translation, the translator needs to be prepared to engage with complexity and search for better alternatives by relentlessly probing the network of possibilities.